On the Right for Lawful Court in Investigation and Search Activities - Andrey Evgenievich Chechetin (Сибирское юридическое обозрение, 2012)
On the basis of the existing federal legislation and decisions of the Constitutional Court of the Russian Federation the author reveals and analyzes jurisdiction of the petition of the agency which conducts investigation and search operations, with the help of an example, i.e. conducting investigation and search operations concerning the judge of the Region Court in Rostov-on-Don with the purpose of verification the information about extortion of a bribe by him.